Arctic meltdown rising seas threatened lands, threatened peoples ([S.l.] : GPI Communication, 1999)
A documentary that explores two remote regions of the world and investigates the problems of climate change from the perspective of two environmentally threatened cultures.
Narrator: Lucy Clayton
Keywords: Global warming; Climatic changes -- Marshall Islands; Climatic changes -- Artic regions